Psychiatry: textbook - Цыганков, Б. Д. психиатрия 19500425 Борис Дмитриевич (Textbook, 2020)
The textbook meets the requirements of the valid State Federal Educational Standard and Psychiatry Curriculum. The textbook contains information on works of outstanding psychiatrists, scientists who not only have identifi ed the basic psychopathological symptoms and syndromes but separated out individual nosological forms of psychoses. In the section dedicated to general psychopathology, descriptive psychopathology in evolutional forming categorical apparatus of the semiotics of mental diseases is expounded. In the section dedicated to specifi c psychiatry, the authors consequently prove the signifi cance of clarity of mental diseases basic defi nitions with analysis of systematization of psychoses and taking into account of the dichotomy nosology-symptomatology and content of ICD-10. It has given the especial matter to the diagnostic and treatment of schizophrenia. Borderline mental disorders (neuroses, posttraumatic stress disorder, psychopathies) are described. The textbook is intended for students of medical institutions of higher education.